2007
DOI: 10.1038/oby.2007.240
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone and Ghrelin Secretion in Severely Obese Women Before and After Bariatric Surgery

Abstract: VALERA MORA, MARIA E., MELANIA MANCO, ESMERALDA CAPRISTO, CATERINA GUIDONE, AMERIGO IACONELLI, DONATELLA GNIULI, GIUSEPPINA ROSA, MENOTTI CALVANI, AND GELTRUDE MINGRONE. Growth hormone and ghrelin secretion in severely obese women before and after bariatric surgery. Obesity. 2007;15:2012-2018. Objective: The objective was to evaluate ghrelin and growth hormone (GH) interactions and responses to a growth hormone-releasing hormone (GHRH)/arginine test in severe obesity before and after surgically-induced weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…This finding supports the hypothesis that although the primary source of ghrelin is the gastric mucosa, small intestinal nutrient exposure is sufficient for food-induced plasma ghrelin suppression in humans and gastric nutrient exposure is not necessary for this suppression [42]. However, different studies have shown an increase [4346] or no change [36, 41, 47] in ghrelin levels after BPD.…”
Section: Ghrelin and Biliopancreatic Diversionsupporting
confidence: 82%
“…This finding supports the hypothesis that although the primary source of ghrelin is the gastric mucosa, small intestinal nutrient exposure is sufficient for food-induced plasma ghrelin suppression in humans and gastric nutrient exposure is not necessary for this suppression [42]. However, different studies have shown an increase [4346] or no change [36, 41, 47] in ghrelin levels after BPD.…”
Section: Ghrelin and Biliopancreatic Diversionsupporting
confidence: 82%
“…However, a number of researchers have found no significant change in ghrelin levels following gastric bypass 31,35,41,57 and BPD, 50,58 and higher ghrelin concentrations have also been reported following both RYGB 4,4850 and BPD. 25,59,60 …”
Section: Search/inclusion Criteria For Studies Of Gut Hormones Followmentioning
confidence: 99%
“…A post-surgical reduction of ghrelin may contribute to the persistent weight loss reported in obese patients following gastric bypass and mixed malabsorptive procedures. However, a number of studies demonstrated no significant change in ghrelin levels following gastric bypass [97,107] and BPD [108], or even higher ghrelin concentrations following both RYGB [109111] and BPD [112114]. …”
Section: Interactions Between Gut Peptides and Brain Systems Relevmentioning
confidence: 99%